The impact of institutionalized representation: creditors' committees and the resolution of corporate liquidation bankruptcies - Jaka Cepec; Peter Grajzl; Barbara Mörec (European Journal of Law and Economics, 2024)
Abstract We utilize micro-level data on corporate liquidation bankruptcies in Slovenia to conduct the first systematic quantitative investigation of the impact of creditors' committees (CCs) on liquidation bankruptcy outcomes. Slovenian law permits, but does not mandate, the establishment of a CC in liquidation bankruptcy proceedings, ensuring variation in CC incidence across cases. To address the non-random formation of CCs, we use propensity score matching and employ a rich set of covariates. Our findings reveal that CCs boost the liquidation value of bankrupt debtors' assets, thereby facilitating recovery, particularly for priority and ordinary unsecured creditors. Additionally, CCs elevate the overall rate of creditors' recovery relative to the value of liquidated assets. However, CCs also prolong the duration of proceedings and increase the likelihood of litigation. Our analysis thus underscores the multifaceted nature of the effect of institutionalized creditor representation on the efficacy of liquidation bankruptcy proceedings.
Additional information: G33;K22;P12;D02
Keywords: 330; Corporate bankruptcy; Liquidation bankruptcy proceedings; Creditors' committees; Debt recovery; Duration; Slovenia; G33; K22; P12; D02